Intimate partner violence in adolescence: Action of the protection network during the COVID-19 pandemic - do Amaral Danilow, Marcella; Gessner Lourenço, Rafaela; Novakovski dos Santos, Thammy; Boza de Melo, Andressa; Tavares, Raquel; Ortelan Soares Amaral, Gabriela; Herreira Trigueiro, Tatiane (O Mundo da Saúde, 2024)
Intimate Partner Violence (IPV) involves violent behavior between formal and occasional partners. Although Curitiba has a Child and Adolescent Protection Network, there are no specific actions to address IPV in this population. It is crucial that healthcare professionals identify and implement interdisciplinary measures to prevent and combat this problem. Therefore, this study aimed to describe and analyze the perception of workers from the Network for the Protection of Children and Adolescents at Risk for Violence in Curitiba regarding the phenomenon of violence between adolescent intimate partners. This is a qualitative study based on the theoretical framework of the Theory of Praxis Intervention in Public Health Nursing. Data were collected in 2022 via semi-structured interviews, subjected to content analysis with the support of WebQDA software. The analytical categories were gender and generation. Five workers from the Protection Network participated and two categories emerged: IPV as a common phenomenon in adolescence and in the territory, and network action in the face of adolescent IPV and limitations during the Covid-19 pandemic. Negative conceptions about adolescent IPV, based on gender and generational stereotypes, often subjugate girls. The fragmented approach in the health services surveyed does not recognize IPV as a health issue, and assistance to adolescents, already deficient, worsened during the pandemic. Despite this, the Protection Network is seen as a hope to combat adolescent IPV, being a promising tool, but it still needs to be more integrated into health services.